Standardization of Turnkey Construction Contracts in Indonesia - Japar, Sugiarto Raharjo (Global Writing Academica Researching & Publishing, 2026)
The rapid expansion of Indonesia's construction sector, particularly in high-rise development, highlights the critical need for effective project management strategies focused on cost control, quality assurance, and timely project completion. This study adopts a normative research approach to investigate the potential benefits, challenges, and implementation strategies for standardizing turnkey construction contracts within Indonesia's specific legal and regulatory context. Standardizing these contracts provides a strategic approach to improving project outcomes and reducing conflicts by clearly defining the roles, responsibilities, and liabilities of all involved parties. The research findings are expected to provide valuable insights for construction stakeholders, policymakers, and legal professionals, thereby fostering greater efficiency, transparency, and accountability in Indonesia's construction industry.